Bacterial Content of Fortified and Unfortified Holder Pasteurized Donor Human Milk During Prolonged Refrigerated Storage. Issue 4 (October 2019) - Mandru, Cosmina; Perrin, Maryanne T.; Iyer, Radha; Liveris, Dionysios; Schwartz, Ira; Alpan, Gad; Parvez, Boriana
ABSTRACT: Objective: To assess the microbial growth in unfortified and fortified Holder pasteurized donor human milk (HPDHM) during 96 hours of refrigerated storage in a clinical setting. Methods: Thirty-six unfortified samples and 77 fortified samples of HPDHM were prepared in a neonatal intensive care milk preparation room and stored in the NICU refrigerator at 4°C to simulate a real-life feeding environment. One milliliter aliquots were removed at 24-hour intervals and cultured in duplicate for bacterial growth on solid blood agar medium. Viable bacterial colonies were characterized using standard microbiological methods. Results: 96.5% of milk samples manipulated in a vertical laminar flow hood were negative for bacterial growth. In the remainder 3.5% of the samples, the maximum growth was 1 colony forming unit/0.1 ml plated. Higher colony counts were observed when the laminar hood was not used. In all cases, the colonies represented common skin bacteria and demonstrated an inconsistent and unsustained growth. Fortifier status and storage time were not significantly associated with increased bacterial growth ( P  > 0.05). Conclusions: Unfortified and fortified HPDHM remain largely free of bacterial growth for up to 96 hours of refrigerated storage in NICU settings. Sample handling techniques are important for preventing microbial contamination.